THE CORRELATION BETWEEN GRAMMAR ACHIEVEMENT AND WRITING ACHIEVEMENT AMONG ELEVENTH GRADE AT SMA BATIK 2 SURAKARTA IN THE ACADEMIC YEAR 2025/2026 - Nadia Aulia Rahman; Sharfina Rahma Wati; Cinthya Dhea Permata; Afra Hana Shofiya; Jihan Nabiila; Naswa Aliya Hasifa (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aimed to determine the correlation between grammar achievement and writing achievement among eleventh-grade students at SMA Batik 2 Surakarta in the 2025/2026 academic year. The research used a quantitative correlational design with purposive sampling involving 31 students. Data were collected through grammar tests and writing assignments assessing content, organization, vocabulary, grammar, and mechanics. The data were analyzed using descriptive statistics, normality tests, Pearson Product Moment correlation, and simple linear regression through Microsoft Excel. The findings showed a weak positive correlation between grammar and writing achievement with a correlation coefficient (r) of 0.310. The coefficient of determination (R²) was 0.096, indicating that grammar achievement contributed only 9.6% to writing achievement, while 90.4% was influenced by other factors. In addition, the significance test revealed a p-value of 0.089, which was higher than 0.05, meaning the correlation was not statistically significant. The statistical outcome showed that the null hypothesis was upheld, while the alternative hypothesis was declined. The study concluded that grammar achievement is not the main factor affecting students’ writing ability because other aspects, such as vocabulary mastery, creativity, motivation, and writing experience, also play important roles.